Research on characterization and modeling for 3D wideband time-varying channels for urban microcells at 2.55 GHz - Shu LI; Xiong-wen ZHAO; Rui ZHANG; Qi WANG; Sui-yan GENG (Tongxin xuebao)
Based on the outdoor microcell MIMO channel measurement campaign at 2.55 GHz,the time-evolution characteristics of three-dimensional wideband channel were studied.The SAGE algorithm was used to extract multipath parameters such as azimuth and elevation angle of departure and arrival.A bidirectional matching algorithm was applied to tracing multipath and the ＆quot;birth-death＆quot; process.The statistical characteristics of multipath birth,lifespan,multipath initial and evolution parameters were analyzed and modeled based on the cross-correlations of multipath parameters.A time-varying channel model with multipath birth-death process was developed.The model parameter table and a detailed flowchart were offered for time-varying channel simulations.The proposed model was validated by comparing the root-mean-square (RMS) of delay spread and angular spread between the simulated and measured results.The channel model proposed can be applied in time-varying channel simulation for urban microcells and it’s also very important to be referred in 5G dynamic channel modeling.